KERAGUAN KRITIS: DESCARTES - Krisna Sukma Yogiswari (Sanjiwani: Jurnal Filsafat, 2019)
Rene Descartes is regarded as the father of modern philosophy, a figure of rationalism, a mathematician, and physiology. Descartes was also a philosopher whose philosophical teachings were very popular because his views which never faltered about the highest truths were in reason or human ratios. Descartes was a philosopher who was dissatisfied with Scholastic philosophy whose views were contradictory, and there was no certainty due to the poor method of thinking.